Molecular Characterization of Community Acquired Staphylococcus aureus Bacteremia in Young Children in Southern Mozambique, 2001–2009 - Vubil, Delfino; Garrine, Marcelino; Ruffing, Ulla; Acácio, Sozinho; Sigaúque, Betuel; Alonso, Pedro L.; von Müller, Lutz; Herrmann, Mathias; Mandomando, Inácio (Frontiers in Microbiology, 2017)
Abstract Background The emergence of community-acquired Staphylococcus aureus infections is increasingly recognized as life threating problem worldwide. In Manhiça district, southern Mozambique, S. aureus is the leading cause of community-acquired bacteremia in neonates. Methods Eighty-four S. aureus isolates from children less than 5 years admitted to Manhiça District Hospital from 2001 to 2009 were randomly selected and genetically characterized by DNA microarray and spa typing. Antimicrobial susceptibility was determined by VITEK 2. Results Thirty-eight different spa types and fourteen clonal complexes (CC) were identified. Spa-type t084 (n=10; 12%) was the most predominant while CC8 (n=18; 21%) and CC15 (n=14; 16%) were the most frequent CCs. Mortality tended to be higher among children infected with CC45 (33.3%, 1/3) and CC8 (27.8%, 5/18). The majority of isolates possessed the accessory gene regulator I (45%) and belonged to either capsule type 8 (52%) or 5 (47%). Panton valentine leukocidin (PVL) encoding genes were detected in 30%. Antibiotic resistance was high for penicillin (89%), tetracycline (59%) and Trimethoprim Sulfamethoxazole (36%) while MRSA was uncommon (8%). Conclusions Although MRSA were uncommon, we found high genetic diversity of methicillin susceptible S. aureus causing bacteremia in Mozambican children, associated with high resistance to the most available antibiotics in this community. Some CCs are likely to be more lethal indicating the need for prompt recognition and appropriate treatment. Key words Staphyloccoccus aureus, bacteremia, molecular characterization, virulence genes, PVL